Contrasting population challenges : St. Lucia and Barbados in the next millennium - St. Bernard, Godfrey ([s.n.] [S.l.], 1998)
Proposes to direct attention toward population challenges that seem most imminent and thus, highly likely to become manifest in Barbados and Saint Lucia during the early years of the 21st century.